P0839EVALUATION OF ECHOCARDIOGRAPHIC INDICES OF DIASTOLIC DYSFUNCTION IN PATIENTS WITH CHRONIC KIDNEY DISEASE. (6th June 2020) - Kourtinos, Alexandros; Pappas, Kostas; Belbasis, Lazaros; DUNI, ANILA; Rapsomanikis, Karolos Pavlos; Kitsos, Athanasios; Katsouras, Christos; Tsiara, Stavroula; Ntounousi, Evangelia
Abstract: Background and Aims: The structure and function of the left ventricle (LV) are affected since the early stages of chronic kidney disease (CKD). Our cross-sectional study aimed to estimate the echocardiographic indices of the LV diastolic function and the evaluation of their potential correlation with indices of kidney injury in patients with CKD, before initiation of renal replacement therapy. Method: 99 patients with CKD (stage 2 CKD: 31 patients (27%), stage 3 CKD: 47 patients (40.9%) and stage 4 CKD: 37 patients (32.1%)) were enrolled in the study. Anthropometric data, indices of renal function (eGFR-CKD-EPI, urinary protein excretion in mg/24h), biochemical laboratory parameters, comorbidities [hypertension (HT), diabetes mellitus (DM), coronary heart disease (CAD)] and echocardiographic indices of LV diastolic function were recorded. In specific, left atrial (LA) dimensions were measured in M-Mode and were expressed both as absolute values in mm as well as indexed to body surface area ((BSA) and expressed as the LA index in mm/m 2 . The study sample, after taking into account patient gender, was further divided into separate groups according to the presence or not of LA dilation. Results: The average patient age was 62 +/- 13 years and average eGFR (CKD-EPI) was 44.1+/-21.4 ml/min/1.73m 2 . With regard to comorbidities, 59.3% of the sample population had arterial hypertension, 24.3% had diabetes mellitus and 10.4% had known coronary artery disease. Regarding anti-hypertensive and hypolipidemic treatment, 22.6% of the patients were on ARB and 24% on ACEi, 51.3% on CCB, 29.6% on β-blockers, 37.4% on diuretics and 28.7% of the patients were receiving statin treatment. 28.2% of the patients had dilated LA in terms of absolute value and 13.8% had dilated LA following indexing to BSA (LA index). A positive correlation was observed between the LA size and age (p=0.001), BMI (p=0.041), uric acid levels (p=0.022), PTH (p=0.029), fibrinogen (p=0.035), LV mass (p=0.006) and LV mass/BSA (p=0.005), whereas a negative correlation was observed with serum LDL (p=0.027). Additionally, there was observed a negative correlation of LA index with eGFR (p=0.05), as well as an inverse relationship between LA index and PTH (p=0.012), age (p=0.004), BMI (p=0.037) and LV mass/BSA (p=0.005). No significant correlations between LA size and LA index with proteinuria or with co-morbidities (DM, HT, CAD) were observed. Conclusion: In a population of patients with stage 2-4 CKD, LA size correlated to indices of CKD. Larger studies are required in order to further confirm these correlations.